C12 Volumetry of Nucleus Caudatus, Lateral Ventricles and Cerebrum of Founder and Second Generation Libechov Transgenic HD Minipigs. (17th September 2014) - Nagelmann, N; Frank, F; Liebsch, L; Schubert, R; Wirsig, M; Schramke, S; Schuldenzucker, V; Juhas, S; Baxa, M; Motlik, J; Marcegaglia, M; Hölzner, E; et al.
Abstract : Background: Transgenic HD minipigs were examined with Magnetic Resonance Imaging for phenotyping the disease model. MRI scans were performed on the founder and second generation of transgenic HD minipigs from the Institute of Animal Physiology and Genetics in Libéchov (Czech Republic). These scans include anatomical, diffusion-weighted and spectroscopic sequences. Aim: For phenotyping, different brain regions of the transgenic HD and wildtype minipigs were investigated periodically. Methods/techniques: Three transgenic HD and two wildtype minipigs were scanned on a 3T Philips Achieva system three times within four years. A 3D gradient echo data set was acquired in 32 min scan time using the following parameters: slices: 450, reconstructed voxel size: 0.5 mm isotropic, FOV: 296 × 296 × 225, NSA: 3, TR: 7.5 ms, TE: 3.4 ms, flip angle: 9 deg. The nucleus caudatus, the lateral ventricles and the cerebrum were segmented semi-manually using the software package "Amira®" and the corresponding volumes were calculated. Results/outcome: So far no significant differences between the transgenic (n = 3) and wildtype (n = 2) group in the analysed volumes were observed. Conclusions/discussion: In this pilot study, no changes in the brain regions assessed were identified. However, the very small number of animals included limits these observations. Due to the slowly progressive nature of HD, changes in the volume between transgenic and wildtype minipigs may be expected to be expressed at later time points. Acknowledgement: Funded by the CHDI Foundation.